Contemporary trends for the treatment of the prisoner in the light of the minimum rules for the treatment of prisoners - الاء محمد رحيم (College of Education for Women, 2019)
The issue of the prisoners' rights and the way of dealing with them is not just a minor or primary issue according to the contemporary attitudes to deal with criminals, but it is a fatal issue that goes with the development of life and comprehension of human rights. As the criminal is considered as a human-being who can be reformed and qualified, according to the aims of the contemporary social service the prisoner is regarded as an idle human source who can be reformed, treated and qualified so as to make him participate to improve his family and society in the end. This study aims at reconstructing the prisons bases when applying the laws of the lowest level of treatment through the research of oppositions, attitudes in some prisons laws in Iraq and among the lowest level rules in treating prisoners and these rules which were accomplished in the first conference of the United States of preservation from crime and Criminals treatment in Geneva convention in 1955. The most important results this study reached are as follows; -Policy of the Iraqi criminal laws still depends on the policy (The Negative Punishment to freedom )as a basic punishment which overcomes its decisions that dominate its decisions. And it was reflected on the prisons positions that we find most of the Iraqi prisons suffer from being over crowded with prisoners. That caused to the unability to classify them ,besides the weakness of education and health service. Consequently ,the reforming states will be far away from its role which is reforming ,qualifying and treating criminals each one according to his case to requalifying them to the society. -Most of the reforming organizations ,especially the managers and the staff (for the reform view)that shows ''Applying the negative punishment to freedom in such circumstances that the reforming and educational attitude become weak and becom costly for both the society and the state equally.